Gaze-eccentricity effects on automobile driving performance -- or -- Going where you look - Readinger, W. O.; Chatziastros, A.; Cunningham, D. W.; Cutting, J. E.; Buelthoff, H. H. (Journal of vision (Charlottesville, Va.), 2010)
Abstract only